A book-by-book guide to New Testament Greek vocabulary - Fresch, Christopher J. (Peabody, Massachusetts : Hendrickson Academic, 2019)
A Book-by-Book Guide to New Testament Greek Vocabulary is intended to help students, pastors, and professors who wish to read a particular book of the Bible in its original language to master the vocabulary that occurs most frequently in the book in question. In contrast to typical Hebrew and Greek vocabulary guides, which present vocabulary words based on their frequency in the Hebrew Bible or New Testament as a whole, this book presents vocabulary words based on their frequency in individual New Testament books, thus allowing readers to understand and engage with the text of a particular book easily and quickly. The book also includes an appendix listing difficult principal parts for selected verbs that occur in the vocabulary lists and providing other advanced notes for additional words in the lists.
Keywords: Bible. -- Language, style; Bible; Greek language, Biblical -- Vocabulary; Greek language, Biblical -- Vocabulary